2017
DOI: 10.1021/acs.accounts.6b00433
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Control of Protein and Cell Interaction with Nanostructured Surfaces by Cluster Assembling

Abstract: The development of smart prosthetics, scaffolds, and biomaterials for tissue engineering and organ-on-a-chip devices heavily depends on the understanding and control of biotic/abiotic interfaces. In recent years, the nanometer scale emerged as the predominant dimension for processes impacting on protein adsorption and cellular responses on surfaces. In this context, the extracellular matrix (ECM) can be seen as the prototype for an intricate natural structure assembled by nanoscale building blocks forming high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
73
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 52 publications
(75 citation statements)
references
References 54 publications
2
73
0
Order By: Relevance
“…According to Schulte et al this incoherent picture can be partially understood by large number of parameters affecting the adsorption process, for example, protein concentration, and by a lack of suitable tools for studying adsorption on rough surfaces. [60] To offset this problem and to correlate adsorption data with topographical surface parameters, Scopelliti et al proposed a quantitative, high-throughput method to conduct a parallel analysis of the protein-surface interaction, while systematically varying surface roughness as well as protein concentration and protein type. [61] The results indicate that the surface nanoscale topography drastically influences the amount of adsorbed proteins; in particular, the saturation uptake increases nonlinearly with increasing nanoroughness.…”
Section: Protein Adsorption Guided By Surface Physicochemical Factorsmentioning
confidence: 99%
“…According to Schulte et al this incoherent picture can be partially understood by large number of parameters affecting the adsorption process, for example, protein concentration, and by a lack of suitable tools for studying adsorption on rough surfaces. [60] To offset this problem and to correlate adsorption data with topographical surface parameters, Scopelliti et al proposed a quantitative, high-throughput method to conduct a parallel analysis of the protein-surface interaction, while systematically varying surface roughness as well as protein concentration and protein type. [61] The results indicate that the surface nanoscale topography drastically influences the amount of adsorbed proteins; in particular, the saturation uptake increases nonlinearly with increasing nanoroughness.…”
Section: Protein Adsorption Guided By Surface Physicochemical Factorsmentioning
confidence: 99%
“…film rq = 15 nm. This particular value of rq was chosen because we recently demonstrated that it induces in PC12 cells mechanotransductive modulations at the level of integrin adhesion complexes and cytoskeleton (Figure 1b), as well as differentiative events, such as neuritogenesis, and a vast change in the cellular program 44,58,64 . Figure 4b; the cross section highlights distinct peaks and valleys at the nanoscale.…”
Section: Characterisation Of the Nanotopographical Colloidal Probesmentioning
confidence: 99%
“…The obtained disordered nanostructured films possess nanotopographical features that resemble those that can be observed in in vivo ECM (e.g. in basement membranes or in the brain 5,6 ) and with nano-3D configurations (in terms of asperity dimensionality and distances) that have a potential to modulate integrin-dependent mechanotransductive processes and signalling 30,44,58,[63][64][65][66][67] ( Figure 1a). Indeed, also in those ECMs whose structure is dominated by fibrillar features, there are often irregularities at the nanoscale, e.g.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations